2021
DOI: 10.1007/s00406-021-01315-2
|View full text |Cite|
|
Sign up to set email alerts
|

Characterising cognitive heterogeneity in individuals at clinical high-risk for psychosis: a cluster analysis with clinical and functional outcome prediction

Abstract: Schizophrenia is characterised by cognitive impairments that are already present during early stages, including in the clinical high-risk for psychosis (CHR-P) state and first-episode psychosis (FEP). Moreover, data suggest the presence of distinct cognitive subtypes during early-stage psychosis, with evidence for spared vs. impaired cognitive profiles that may be differentially associated with symptomatic and functional outcomes. Using cluster analysis, we sought to determine whether cognitive subgroups were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 67 publications
3
2
0
Order By: Relevance
“…Interestingly, patients of the severely impaired cluster also showed lower general functioning scores at a trend at 6- and 12-month follow-up. Similar results were reported by Haining and colleagues [74]. Tan and colleagues [75] on the other hand did not find associations between the three cognitive clusters and symptom expression, but found that the cognitively impaired subgroup already showed worse academic performance at the level of childhood, early and late adolescence.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Interestingly, patients of the severely impaired cluster also showed lower general functioning scores at a trend at 6- and 12-month follow-up. Similar results were reported by Haining and colleagues [74]. Tan and colleagues [75] on the other hand did not find associations between the three cognitive clusters and symptom expression, but found that the cognitively impaired subgroup already showed worse academic performance at the level of childhood, early and late adolescence.…”
Section: Discussionsupporting
confidence: 87%
“…Tan and colleagues [75] on the other hand did not find associations between the three cognitive clusters and symptom expression, but found that the cognitively impaired subgroup already showed worse academic performance at the level of childhood, early and late adolescence. These findings confirm the critical relevance of cognitive deficits for early detection and functional prediction [2628, 74]. This often replicated distribution of a severely impaired cluster, indicating that early interventions based on such cluster analysis would be suitable too.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“… 14 Applying machine learning techniques to large clinical data-sets provides an opportunity to explore data in novel ways and generate new insights. 15 One such technique is cluster analysis, which is the method of delineating distinct subgroups in a data-set such that the features of one group are more similar to each other than the features of another group. 16 Clustering has been used to identify clinically meaningful groupings of patients within heterogeneous populations, including people in intensive care, 17 people with diabetes, 18 people with psychosis 5 and people with autism.…”
Section: Research Using Routinely-collected Clinical Datamentioning
confidence: 99%
“…Impaired cognitive functioning is a major symptom of schizophrenia and is associated with poor prognosis and quality of life in affected individuals 1 , 2 . Considerable variability in cognition has been reported in individuals with schizophrenia across different illness courses and in individuals at high risk of psychosis 3 7 , which poses challenges for developing effective interventions. Additionally, previous research 8 , 9 indicates that antipsychotics may impact the cognitive function of individuals with schizophrenia, emphasizing the complexity of discovering biomarkers for cognition-related therapy.…”
Section: Introductionmentioning
confidence: 99%